1999
DOI: 10.1111/1467-8535.00089
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive style, gender and learning from multi‐media materials in 11‐year‐old children

Abstract: Eighty 11-year-old pupils (40 males and 40 females) from an urban primary school were assessed for cognitive style by means of the Cognitive Styles Analysis which indicated their positions on each of the two style dimensions, the Wholist-Analytic and the Verbal-Imagery. They then studied parts of three CD-ROM multi-media packages on science topics and after each, completed a multiple choice recall test. An indication of their performance on traditionally taught science was taken to be the performance on scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 12 publications
2
79
1
4
Order By: Relevance
“…The first presents items containing pairs of complex geometrical figures that the individual is required to judge as either the same or different. The second presents items each comprising a simple geometrical shape, such as a square or a triangle, and a complex geometrical figure, as in the GEFT, and the individual is asked to indicate whether or not the simple shape is contained in a complex one by pressing one of two marked response keys (Riding and Grimley, 1999).. The first sub-test is a task requiring Field Dependent capacity.…”
Section: Cognitive Styles Analysismentioning
confidence: 99%
“…The first presents items containing pairs of complex geometrical figures that the individual is required to judge as either the same or different. The second presents items each comprising a simple geometrical shape, such as a square or a triangle, and a complex geometrical figure, as in the GEFT, and the individual is asked to indicate whether or not the simple shape is contained in a complex one by pressing one of two marked response keys (Riding and Grimley, 1999).. The first sub-test is a task requiring Field Dependent capacity.…”
Section: Cognitive Styles Analysismentioning
confidence: 99%
“…The first presents items containing pairs of complex geometrical figures that the individual is required to judge as either the same or different. The second presents several items each comprising a simple geometrical shape, such as a square or a triangle, and a complex geometrical figure, as in the GEFT, and the individual is asked to indicate whether or not the simple shape is contained in a complex one by pressing one of two marked response keys (Riding & Grimley, 1999). These two subtests have different purposes.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…According to [4], the inability of schools and teachers to take account of preferences produces endemic low achievement and poor motivation. There are empirical researches as shown by [5], [6], [7] suggest that learning styles can enhance academic performance in several respects. Analyses of the learning styles of non-achieving students have revealed that, as a group, such students learn in a style and with instructional strategies that differ significantly from those of students who perform well in school [8].…”
Section: Introductionmentioning
confidence: 99%